A Review of The Performance of Artificial Intelligence In The Analysis of Chest CTs For The Diagnosis of COVID-19 - Golchinheydari, Sirous (Journal of Biomedical and Pharmaceutical Research, 2022)
During the COVID-19 pandemic, chest CTs was used as an alternative for diagnosis of COVID-19. This resulted in the use of artificial intelligence as an independent assessor and in aiding the radiologist in the diagnosis of COVID-19. In this short review, we assessed the accuracy, sensitivity and specificity of AI software employed. The average accuracy, sensitivity and specificity were found to be 94.38%, 91.64% and 91.10% respectively. Despite the limitations of AI, it proved to be a valuable and reliable tool in diagnosis of COVID-19